Ligasure Hemorrhoidectomy Versus Milligan Morgan Hemorrhoidectomy Prospective Randomized Study - Ahmed Mustafa Ahmed (Diyala Journal of Medicine, 2024)
Background: Hemorrhoidectomy is a frequently performed surgical procedure associated with postoperative pain. The use of Ligasure could result in a decreased incidence of pain and bleeding, as coagulation with high-frequency currency has minimal thermal spread and limited tissue damage. Objective: The research compares Ligasure pile excision with surgical diathermy excision for the treatment of III-IV-grade piles. Patients and Methods: Eighty patients with pile III or IV degrees were randomized into two groups: Group one (LS) and group two (diathermy). The study evaluates the mean postoperative pain, intraoperative bleeding, and intraoperative time requirement, early and late complications. All patients were followed up for of 10-12 months. Results: The operating time is considerably shortened in Ligasure group (LS); postoperative pain disappears earlier in LS than in diathermy. Additionally, there was less intraoperative bleeding in LS, and short duration hospital stay as compared to diathermy group. Conclusion: LS is an efficient procedure in degree III or IV pile excision. Therefore, the procedure enhances the use of LS as one of the acceptable modality surgical options for grade III–IV pile. Keywords: Hemorrhoidectomy, ligasure™ vessel sealing system, milligan morgan technique.